2022
DOI: 10.1021/acs.est.1c07510
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive and Specific Responses of Oyster Hemocytes to Copper Exposure: Single-Cell Transcriptomic Analysis of Different Cell Populations

Abstract: Oyster hemocytes are the primary vehicles transporting and detoxifying metals and are regarded as important cells for the occurrence of colored oysters due to copper (Cu) contamination. However, its heterogeneous responses under Cu exposure have not been studied. Single-cell transcriptome profiling (scRNA-seq) provides high-resolution visual insights into tissue dynamics and environmental responses. Here, we used scRNA-seq to study the responses of different cell populations of hemocytes under Cu exposure in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 66 publications
2
27
0
Order By: Relevance
“…Zinc-contaminated oysters C. hongkongensis showed increase of granulocyte mortality, which suggested that granulocytes were the most sensitive cell type in responding to Zn; moreover, the granulocyte number decreased whereas those of semigranulocytes and agranulocytes increased (158). In the same species, specific responses of granulocyte, semigranulocyte and hyalinocyte have been detected to copper; granulocyte was the most important responsive cell type and displayed heterogeneity responses of its two distinguished subtypes (385). In the oyster C. gigas, granulocyte percentage increased in the presence of hydrocarbons, which led authors to hypothesise that granulocytes may be more resistant than hyalinocytes (345).…”
Section: Abiotic Stress: Temperature Salinity Acidification Hypoxia A...mentioning
confidence: 95%
“…Zinc-contaminated oysters C. hongkongensis showed increase of granulocyte mortality, which suggested that granulocytes were the most sensitive cell type in responding to Zn; moreover, the granulocyte number decreased whereas those of semigranulocytes and agranulocytes increased (158). In the same species, specific responses of granulocyte, semigranulocyte and hyalinocyte have been detected to copper; granulocyte was the most important responsive cell type and displayed heterogeneity responses of its two distinguished subtypes (385). In the oyster C. gigas, granulocyte percentage increased in the presence of hydrocarbons, which led authors to hypothesise that granulocytes may be more resistant than hyalinocytes (345).…”
Section: Abiotic Stress: Temperature Salinity Acidification Hypoxia A...mentioning
confidence: 95%
“…Single cell transcriptome technology has been widely used in the research on the properties of the organ and tissue cells in plants and animals ( 30 32 ). Meanwhile, the successful applications of scRNA-seq on invertebrate hemocytes from Drosophila , mosquitoes and oysters have established the basis for scRNA-seq studies on shrimp and further revealed the significance of characterizing the functional properties of hemocytes at the single-cell transcriptional level ( 33 35 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such new age of knowledge at the cellular resolution, thanks to single-cell omics, is just starting to emerge in the environmental sciences. 4 10 …”
mentioning
confidence: 99%
“…Linking biology and chemistry is at the core of environmental sciences, and it is now possible to study comprehensive cell signatures by means of single-cell approaches. The trend toward the analysis of increasingly smaller samples, eventually reaching nanosamples and even single-cell approaches, has resulted in massive data sets. The measures at cellular level, at higher temporal and spatial scale resolution, require significant methodological development, but allows for new questions with eventual knowledge breakthroughs.…”
mentioning
confidence: 99%
See 1 more Smart Citation